Congenital Factor XI Deficiency: An Update - Duga, Stefano; Salomon, Ophira (Seminars in Thrombosis and Hemostasis, 2013)
Severe factor XI (FXI) deficiency is an injury-related bleeding disorder, common in Ashkenazi Jews (with two mutations prevailing), but rare worldwide (with heterogeneous mutations). In the past two decades, more than 220 mutations in the FXI gene have been reported in patients with FXI deficiency, of which 7 showed a founder effect. Inhibitors to FXI were described in patients with null-allele mutations, following exposure to plasma, FXI concentrates, or anti-RhD immunoglobulin. Treatment of patients with severe FXI deficiency remains challenging because factors influencing bleeding risks are still unknown. The use of lower doses of recombinant activated factor VII in comparison with the doses commonly applied in hemophilia A or B seems promising also when assessed in vitro by thrombin generation test. Recently, FXI has been shown to have a separate role in hemostasis and in thrombosis. In animal models, targeting FXI by knocking out the gene or by using FXI-neutralizing antibodies, antisense oligonucleotides, and peptidomimetic inhibitors, prevents arterial and vein thrombosis. The homology between human and murine FXI and the significant antithrombotic effect of FXI deficiency in animal models resulted in the development of a novel approach of targeting FXI for prevention of thrombosis without impairing hemostasis in high-risk patients. The acceptance of FXI as a risk factor for thrombosis is a new concept, and patients with severe FXI deficiency might gain profit during life course.
Keywords: factor XI; inhibitors; bleeding; thrombosis; antithrombosis; animal models; global coagulation test; genetics; molecular diagnosis